The Law and Impact of Political Corruption on Community Trust In Political Parties In Indonesia - Moh Ali Wafa; Sudirman Abbas; Umar Sulaiman (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
This study aims at examining the law and impact of corrupt politician behavior on public trust in political parties and the efforts of reforms by the parties. Using the survey method, this study has come to the following conclusions. (1) the corruption committed by politicians mostly occurs due to the work pattern and the Indonesian political system which develops towards political apathy, in which regeneration does not optimally take place, while the drive to maintain power and dominate the political parties in the state system is increasing; (2) the corruption does not only influence the public trust in political parties, but also the perspective and paradigm of society towards the political system and government in Indonesia. (3) The impact of this political apathy, which we might be able to see from how the radicalism and extremism easily exist and develop in Indonesia. An encouragement to even create a new system is present from this political apathy. If this is not immediately corrected, a change in the system in Indonesia can probably occur.Keywords: Law; Corruption; Politicians; Political Parties; Community Trust Hukum dan Dampak Korupsi Politik Terhadap Kepercayaan Masyarakat Pada Partai Politik di Indonesia AbstrakPenelitian ini bertujuan untuk mengkaji hukum dan dampak perilaku politikus korup terhadap kepercayaan publik terhadap partai politik dan upaya reformasi yang dilakukan oleh partai tersebut. Dengan menggunakan metode survei, penelitian ini menghasilkan kesimpulan sebagai berikut. (1) Korupsi yang dilakukan oleh politikus sebagian besar terjadi karena pola kerja dan sistem politik Indonesia yang berkembang ke arah apatisme politik, dimana regenerasi tidak berlangsung secara optimal, sedangkan dorongan untuk mempertahankan kekuasaan dan mendominasi partai politik dalam sistem ketatanegaraan. meningkat; (2) Korupsi tidak hanya mempengaruhi kepercayaan publik terhadap partai politik, tetapi juga cara pandang dan paradigma masyarakat terhadap sistem politik dan pemerintahan di Indonesia. (3) Dampak dari sikap apatis politik ini, yang mungkin dapat kita lihat dari betapa mudahnya radikalisme dan ekstrimisme tumbuh dan berkembang di Indonesia. Dorongan untuk bahkan menciptakan sistem baru hadir dari sikap apatis politik ini. Jika tidak segera diperbaiki, perubahan sistem di Indonesia kemungkinan besar bisa terjadi.Kata Kunci: Hukum; Korupsi; Politisi; Partai Politik; Kepercayaan Masyarakat Закон и влияние политической коррупции на доверие общества политическим партиям в Индонезии АннотацияЭто исследование направлено на изучение закона и влияния коррумпированного поведения политиков на общественное доверие политическим партиям и усилия партий по проведению реформ. Используя метод опроса, это исследование пришло к следующим выводам: (1) коррупция, совершаемая политиками, в основном происходит из-за модели работы и политической системы Индонезии, которая развивается в сторону политической апатии, при которой возрождение не происходит оптимально, в то время как стремление сохранить власть и доминировать над политическими партиями в государственной системе повышается; (2) коррупция влияет не только на доверие общества политическим партиям, но также на взгляды и парадигму общества в отношении политической системы и правительства в Индонезии; (3) влияние этой политической апатии, которое мы могли бы увидеть по тому, как радикализм и экстремизм легко существуют и развиваются в Индонезии. Эта политическая апатия дает стимул даже к созданию новой системы. Если это немедленно не исправить, вероятно, произойдут изменения в системе в Индонезии.Ключевые слова: Закон; коррупция; политики; политические партии; общественное доверие